1999
DOI: 10.1016/s0960-9822(99)80370-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of sperm competition and sperm storage in Drosophila

Abstract: Drosophila females engage in multiple matings [1] [2] [3] [4] even though they can store sperm in specialized organs for most of their life [5]. The existence of sperm competition in Drosophila has been inferred from the proportion of progeny sired by the second male in double-mating experiments [6] [7] [8]. Investigators have used this approach to quantify genetic variation underlying sperm competition [8] [9] [10], to elucidate its genetic basis [11], to identify the dependence of different male competitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
59
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 20 publications
2
59
2
1
Order By: Relevance
“…1; Fisher's PLSD, critical difference ¼ 0.16, difference ¼ 0.17, P ¼ 0.04) because remated females received new viable sperm from the copulating male. Therefore, contrary to previous assumptions [7][8][9] , incoming seminal fluid does not cause resident sperm death and, instead, sperm physiology is influenced by sperm storage rather than seminal fluid. Previous research has found that 'incapacitation' is more effective on older resident sperm 8 , but how males could incapacitate rival sperm without damaging their own is unknown, especially because there is no self-sperm recognition 10 .…”
contrasting
confidence: 66%
See 4 more Smart Citations
“…1; Fisher's PLSD, critical difference ¼ 0.16, difference ¼ 0.17, P ¼ 0.04) because remated females received new viable sperm from the copulating male. Therefore, contrary to previous assumptions [7][8][9] , incoming seminal fluid does not cause resident sperm death and, instead, sperm physiology is influenced by sperm storage rather than seminal fluid. Previous research has found that 'incapacitation' is more effective on older resident sperm 8 , but how males could incapacitate rival sperm without damaging their own is unknown, especially because there is no self-sperm recognition 10 .…”
contrasting
confidence: 66%
“…In addition to generating competition between the ejaculates of different males 1,2 , multiple mating may allow females to bias sperm use 3,4 .I nDrosophila melanogaster, the last male to inseminate a female sires approximately 80% of subsequent progeny 5 . Both sperm displacement, where resident sperm are removed from storage by the incoming ejaculate of the copulating male 6 , and sperm incapacitation, where incoming seminal fluids supposedly interfere with resident sperm 7 , have been implicated in this pattern of sperm use [5][6][7][8][9][10][11][12] . But the idea of incapacitation is problematic because there are no known mechanisms by which an individual could damage rival sperm and not their own.…”
mentioning
confidence: 99%
See 3 more Smart Citations